Identification of Regulatory circRNAs Involved in the Pathogenesis of Acute Myocardial Infarction - Zhao, Cuimei; Liu, Jingjing; Ge, Wen; Li, Zhi; Lv, Mengwei; Feng, Yipeng; Liu, Xuebo; Liu, Ban; Zhang, Yangyang (Frontiers in Genetics, 2021)
BACKGROUND: Acute myocardial infarction (AMI) has high morbidity and mortality worldwide. However, the pathogenesis of AMI is still unclear and the impact of circular RNAs (circRNAs) on AMI has been rarely recognized and needs to be explored. MATERIAL AND METHODS: The circRNA array was applied to investigate the expression level of circRNAs in the blood samples of coronary arteries of three AMI patients and three normal persons. Principal component analysis (PCA)and unsupervised clustering analysis were performed to reveal the distinguished expression patterns of circRNAs. The miRNA expression profiles of AMI patients were identified from a public dataset from Gene Expression Omnibus (GEO) database (GSE31568). The miRNA binding sites on the circRNAs were predicted by miRanda. The miRNA enrichment analysis and annotation tool were used to explore the pathways that the dysregulated circRNAs may participate in. RESULTS: Totally, 142 differentially-expressed circRNAs, including 89 up-regulated and 53 down-regulated in AMI samples, were identified by the differential expression analysis. AMI patients had quite different circRNA expression profiles from those of normal controls. Functional characterization revealed that circRNAs that had the potential to regulate miRNAs were mainly involved in seven pathways, such as the Runt-related transcription factor-1 (RUNX1) expression and activity-related pathway. Specifically, hsa_circRNA_001654, hsa_circRNA_091761, hsa_circRNA_405624, and hsa_circRNA_406698 were predicted to sponge four miRNAs including hsa-miR-491-3p, hsa-miR-646, hsa-miR-603 and hsa-miR-922, thereby regulating RUNX1 expression or activity. CONCLUSIONS: We identified dysregulated blood circRNAs in the coronary arteries of AMI patients, and predicted that four up-regulated circRNAs that were involved in the regulation of RUNX1 expression or activity through sponging four miRNAs. Keywords: Acute Myocardial Infarction; circRNA; miRNA; Functional characterization; Runt-related transcription factor-1.